2011
DOI: 10.1080/10286608.2011.637624
|View full text |Cite
|
Sign up to set email alerts
|

Influence of climate change on the energy efficiency of light-weight steel residential buildings

Abstract: This paper addresses the influence of the climate change scenarios predicted by the Intergovernmental Panel for Climate Change (IPCC) for Southern Europe and the Mediterranean region on the energy efficiency of light-weight steel residential buildings. A performance-based approach is adopted to carry out this assessment using advanced dynamic simulation of the operational energy performance. Based on a typical Portuguese cold-formed steel residential building, a representative numerical model is calibrated aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…Santos et al [210] Kendrick et al [211] suggested that lightweight construction may lead to higher internal temperatures during the summer, particularly in the warmer future scenarios, due to the lack of thermal mass. The problem of summer overheating in a low-energy steel frame house was also evaluated by Rodrigues et al [212].…”
Section: Energy Consumption and Thermal Comfort Of Lsf Buildingsmentioning
confidence: 99%
“…Santos et al [210] Kendrick et al [211] suggested that lightweight construction may lead to higher internal temperatures during the summer, particularly in the warmer future scenarios, due to the lack of thermal mass. The problem of summer overheating in a low-energy steel frame house was also evaluated by Rodrigues et al [212].…”
Section: Energy Consumption and Thermal Comfort Of Lsf Buildingsmentioning
confidence: 99%
“…LSF has become increasingly popular in small and medium-sized residential buildings, offering some distinct advantages over traditional construction in such fields as sustainability, cost-effectiveness, constructive process, and safety at work. As a consequence of this popularity increase, the number of companies specialized in this type of construction has been increasing, leading to more competitive prices [3].…”
Section: Lsf System Advantagesmentioning
confidence: 99%
“…For this large percentage, the main contributions come from cooling and heating, 55% to 74%, depending on the climatic region [3] and hot water production. Therefore, it is imperative to develop and/or optimize constructive solutions and methods that offer clear advantages in reducing the energy costs of buildings during this stage of their life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some additional case studies related to LSF buildings thermal behaviour and energy eiciency will be described, namely the "Afordable Houses" research project [5,6], a parametric study regarding the thermal performance of LSF houses in Csb climatic regions [28], the impact of climate change on the energy eiciency of a LSF residential building [9] and the optimization of incorporation of PCMs in LSF houses in diferent climates [25].…”
Section: Case Studiesmentioning
confidence: 99%
“…The parameters with inluence on thermal performance and energy eiciency of LSF buildings could be grouped into four key factors [1]: climate [8,9]; building envelope; occupants behaviour; and buildings systems. In Section 4 of this chapter, each one of these key factors will be further analysed.…”
Section: Introductionmentioning
confidence: 99%